(untitled) (Journal of Innovative Research, 2025)
This study examines the relationship between street trading points and traffic volume in Gombe Central Business District (CBD) thereby investigating its implications for urban planning and policy. The study highlights the dual role of street trading as a vital informal economic sector that generates livelihoods while simultaneously contributing to traffic problems. Using a mixed-method approach, the research analyzes data collected from 939 respondents who are either street traders or non-street traders in order to evaluate their socio-economic characteristics, and how the activities within the street trading points affects traffic volume. Findings reveals that street trading points are majorly owned and patronized by the male gender in the study area. It also reveals a significant correlation between increased traffic volume and vehicular time delays, indicating that the occupation of streets by the street and non- street traders exacerbates traffic congestion. The study underscores the need for targeted urban planning strategies that balance the support for informal economic activities such as street trading with effective traffic management to enhance urban mobility and public safety. Recommendations include designating specific trading zones, implementing regulatory frameworks, and improving infrastructure to accommodate both street traders, pedestrians and vehicular traffic.